Multidiscpinary Approach in Nasopharyngeal Cancer - Kodrat, Henry (Medicinus, 2016)
Nasopharyngeal cancer (NPC) is endemic in Indonesia. The purpose of the review is to describe the risk factors, clinical symptoms, diagnostic procedures and staging, management and treatment options, and follow-up. Multi-disciplinary approach to the NPC not only for treatment, but also has been started from the diagnosis proccess. The multidisciplinary approach also plays role after treatment, especially for the follow-up and rehabilitation of post-treatment toxicity.Keywords: cancer, nasopharynx, radiotherapy.